СТРУКТУРНО-СЕМІОТИЧНИЙ ПІДХІД ДО ВИЗНАЧЕННЯ СИСТЕМИ МИСТЕЦЬКО-ПЕДАГОГІЧНИХ ЗНАНЬ (Педагогіка вищої та середньої школи, 2022)
The article deals with the problem of using structure-semiotic approach to the determining of system o f art-pedagogical knowledge and perspective of its further research.